2016
DOI: 10.1103/physrevd.94.026006
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and entanglement entropy with Weyl corrections

Abstract: We consider charged black holes in four dimensional AdS space, in the presence of a Weyl correction. We obtain the solution including the effect of back-reaction, perturbatively up to first order in the Weyl coupling, and study its thermodynamic properties. This is complemented by a calculation of the holographic entanglement entropy of the boundary theory. The consistency of results obtained from both computations is established.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 44 publications
5
54
0
Order By: Relevance
“…Since exact solution is difficult to find, here we will try to find the solution perturbatively by treating the Weyl coupling constant γ as a small perturbative parameter. In four dimensions, linear order solution in γ was found in [43] and main purpose here is to find the solution for all spacetime dimensions. Our second aim is to find the black hole solution in higher order in γ and show that the corrections due to higher order are small, and that the linear order analysis is trustable.…”
Section: Jhep04(2016)142mentioning
confidence: 99%
“…Since exact solution is difficult to find, here we will try to find the solution perturbatively by treating the Weyl coupling constant γ as a small perturbative parameter. In four dimensions, linear order solution in γ was found in [43] and main purpose here is to find the solution for all spacetime dimensions. Our second aim is to find the black hole solution in higher order in γ and show that the corrections due to higher order are small, and that the linear order analysis is trustable.…”
Section: Jhep04(2016)142mentioning
confidence: 99%
“…It was found that the entanglement entropy can characterize the related phase transition for a charged AdS black hole. Further studies on holographic entanglement entropy and its relation to phase transition have been done for various AdS black holes in [35][36][37][38]. For the AdS phantom black hole presented in this paper, we will further show such a relation which keeps valid even for the case with the Ricci flat horizon black hole.…”
Section: Introductionmentioning
confidence: 99%
“…To further confirm the similarity of the phase structure between the thermal entropy and entanglement entropy, [42] checked Maxwell's equal area law 3 later and found that it held for the first order phase transition in the entanglement entropytemperature plane. Now [40] has been generalized to the extended phase space [43], massive gravity [44], as well as Weyl gravity [45], and all the results showed that the entanglement entropy exhibited the same phase structure as that of the thermal entropy.…”
Section: Introductionmentioning
confidence: 99%